Customer Satisfaction and Brand Loyalty in the Petrol Bike Market: A Study on Young Riders' Preferences and Expectations - Subedi, Sandesh (NPRC Journal of Multidisciplinary Research, 2024)
Introduction: Satisfaction is a person's feelings of pleasure or disappointment resulting from a comparison of a product's perceived performance with expectations. As the definition indicates, satisfaction is a function of perceived performance and expectations. If the performance does not meet the customer's expectations, the customer is dissatisfied. If the performance exceeds expectations, the customer is very satisfied or happy. There has been a noticeable shift in the petrol bike market from a buyer's market to a seller's market, with plenty of choice. Players have to operate on various fronts such as pricing, technological product design, productivity, after-sales service, marketing and distribution. In the short term, the market shares of individual producers are sensitive to capacity, product acceptance, prices and competitive pressures from other producers.Methods: The research approach used is quantitative research approach in which each of the statements and questions have been provided with certain scores. The total of 123 respondents were taken to conduct the research. A structured questionnaire was designed based on five-point Likert scale.Findings: In terms of gender, the male population (89.4%) was greater than female population (10.6%). In accordance of age, the majority of people where from age group 18-25 (71.5%). According to the collected data (49.6%) of respondents ride their bike daily.Conclusion: According to the report, petrol bikes are most popular among young people, particularly from manufacturers such as Hero, Honda, Bajaj and KTM. Many users are satisfied with their bikes and would suggest them to others, but they believe they may be improved in terms of speed, fuel efficiency, noise, and lighting. Companies can increase customer satisfaction by enhancing these elements. Focusing on these improvements and marketing to young male riders may help these brands flourish.